A multicenter randomized controlled trial of zephyr endobronchial valve treatment in heterogeneous emphysema (TRANSFORM) - Kemp, Samuel V.; Eberhardt, Ralf; Herth, Felix (American journal of respiratory and critical care medicine, 2017)
Rationale: Single-center randomized controlled trials of the Zephyr endobronchial valve (EBV) treatment have demonstrated benefit in severe heterogeneous emphysema. This is the first multicenter study evaluating this treatment approach.Objectives: To evaluate the efficacy and safety of Zephyr EBVs in patients with heterogeneous emphysema and absence of collateral ventilation.Methods: This was a prospective, multicenter 2:1 randomized controlled trial of EBVs plus standard of care or standard of care alone (SoC). Primary outcome at 3 months post-procedure was the percentage of subjects with FEV1 improvement from baseline of 12% or greater. Changes in FEV1, residual volume, 6-minute-walk distance, St. George’s Respiratory Questionnaire score, and modified Medical Research Council score were assessed at 3 and 6 months, and target lobe volume reduction on chest computed tomography at 3 months.Measurements and Main Results: Ninety seven subjects were randomized to EBV (n = 65) or SoC (n = 32). At 3 months, 55.4% of EBV and 6.5% of SoC subjects had an FEV1 improvement of 12% or more (P < 0.001). Improvements were maintained at 6 months: EBV 56.3% versus SoC 3.2% (P < 0.001), with a mean ± SD change in FEV1 at 6 months of 20.7 ± 29.6% and −8.6 ± 13.0%, respectively. A total of 89.8% of EBV subjects had target lobe volume reduction greater than or equal to 350 ml, mean 1.09 ± 0.62 L (P < 0.001). Between-group differences for changes at 6 months were statistically and clinically significant: ΔEBV-SoC for residual volume, −700 ml; 6-minute-walk distance, +78.7 m; St. George’s Respiratory Questionnaire score, −6.5 points; modified Medical Research Council dyspnea score, −0.6 points; and BODE (body mass index, airflow obstruction, dyspnea, and exercise capacity) index, −1.8 points (all P < 0.05). Pneumothorax was the most common adverse event, occurring in 19 of 65 (29.2%) of EBV subjects.Conclusions: EBV treatment in hyperinflated patients with heterogeneous emphysema without collateral ventilation resulted in clinically meaningful benefits in lung function, dyspnea, exercise tolerance, and quality of life, with an acceptable safety profile.Clinical trial registered with www.clinicaltrials.gov (NCT02022683).